ANALYZING THE INTERACTION OF CITIZENSHIP, PHILANTHROPY, AND STATE RELATIONS IN THE SOCIOCULTURAL CONTEXT - Arpannudin, Iqbal (Integralistik, 2024)
This study set out to investigate how the state and its citizens create their connection under the framework of philanthropy. In order to identify the pattern of interactions between the public, the government, and the charitable movement, this study employed a grounded theory methodology. The study's findings suggested that, in terms of the state's constitutionally imposed duties to its citizens, aiding their welfare—which the state actively pursued—was not so much philanthropy as it was an obligation to the people. The argument we could make was that the government, philanthropic institutions, and citizens should work together to establish a complementary meeting point. This is because the government is responsible for attending to the basic needs of the community, while foreign philanthropic institutions concentrate on empowering other domains, like advocacy.